2011
DOI: 10.1177/0305735611422672
|View full text |Cite
|
Sign up to set email alerts
|

The influence of distracting familiar vocal music on cognitive performance of introverts and extraverts

Abstract: This study investigates the effect of familiar musical distractors on the cognitive performance of introverts and extraverts. Participants completed a verbal, numerical and logic test in three music conditions: vocal music, instrumental music and silence. It was predicted that introverts would perform worse with vocal music, better with instrumental music and even better in silence across all tests while for extraverts it would be the reverse. Results showed that during the verbal test, overall performance for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 33 publications
4
43
2
Order By: Relevance
“…Background music is reported to facilitate socially constructive and sociodramatic play (Love & Burns, 2007), positive child-to-child interactions (Godeli et al1996) and to have a positive influence on aspects of children's cognition, including mathematics test scores (Rauscher, Shaw, & Ky, 1993b). Some studies of older children's reading performances indicated the positive effect of background music (Carlson, Hoffman, Gray, & Thompson, 2004;Schellenberg, Nakata, Hnter, & Tamoto, 2007), whilst others report a negative effect (Anderson & Fuller, 2010;Avila, Furnham & McClelland, 2011;Boyle & Coltheart, 1996), or no significant difference concerning whether music was being played in the background or not (Johansson, Holmqvist, Mossberg & Lindgren, 2011).…”
mentioning
confidence: 99%
“…Background music is reported to facilitate socially constructive and sociodramatic play (Love & Burns, 2007), positive child-to-child interactions (Godeli et al1996) and to have a positive influence on aspects of children's cognition, including mathematics test scores (Rauscher, Shaw, & Ky, 1993b). Some studies of older children's reading performances indicated the positive effect of background music (Carlson, Hoffman, Gray, & Thompson, 2004;Schellenberg, Nakata, Hnter, & Tamoto, 2007), whilst others report a negative effect (Anderson & Fuller, 2010;Avila, Furnham & McClelland, 2011;Boyle & Coltheart, 1996), or no significant difference concerning whether music was being played in the background or not (Johansson, Holmqvist, Mossberg & Lindgren, 2011).…”
mentioning
confidence: 99%
“…One simple and effective way is to improve the stage performance. Stage to divert the attention of the concert, which will come from the stage and audience pressure into how vocal singing and performing perfectly, auditory and visual feast bring an audience, through singing the change of thought into the stage singing confidence [7]. Such as "the audience will not because I am not good enough and intense reaction", "the audience is not interested in singing to me", "the audience is not care about my dress" into "how to sing to attract the audience's applause and cheers", "how to inspire the audience to sing interest", this concert will be able to divert attention from the audience to the stage, performing and relaxing.…”
mentioning
confidence: 99%
“…Based on the combined results from rated questionnaires about music familiarity and perceived level of distractions, the authors concluded that familiarity with song lyrics produces a small but non-significant effect on performance and that people have poor assessments of the degree of WM performance degradation resulting from irrelevant background noise. Consistent with the above study, Avila, Furnham, and McClelland (2012) assessed the effects of familiar vocal and instrumental music on the cognitive performance in verbal, numerical, and logic tests of 58 subjects. Instrumental and vocal versions of music pieces were identical except for the absence of vocals in the instrumental version.…”
Section: Chapter 2 Literature Review the Effect Of Background Musicmentioning
confidence: 88%
“…While most studies show that listening to instrumental and vocal music impairs performance of a cognitive task (Alley & Greene, 2008;Avila, Furnham, & McClelland, 2012;Cassidy & MacDonald, 2007;Furnham & Bradley, 1997;Salame & Baddeley, 1982;Smith, 1985;Stroupe, 2005), a few studies suggest that background music does not interfere with performance. For example, teenagers and college students have expressed lower levels of concentration and higher levels of distraction during academic assignments while listening to certain kinds of music (Jones, 2010;Schellenberg & Weiss, 2013).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation